The Use of Mind Mapping Technique In Improving Students’ Writing Ability at SMA Al-Khazanah Tidore Kepulauan - Rosalina Silulu; Vebiyanti Nasir (Jurnal Ilmiah Wahana Pendidikan, 2022)
The research aims to see the using of mind mapping techniques in improving students’ writing ability. The subjects are 16 students of grade XI at SMA Al-Khazanah and the type of this research is quantitative. The data are gained by assessing the students’ writing ability through the post-test in control class and experimental class. The data analysis is using t-test by determining mean and standard error of both variables. T-test is used to see the difference between the result and t-table. The result of the research showed that the hypothesis null (Ho) are rejected and hypothesis alternative (Hi) are accepted because the t-observation (5,062) higher than t-table (1,895). It can be concluded that mind mapping had positive effect toward students’ writing ability. Mind mapping made students’ more active and creative in shared their ideas in writing English